Dislocation: Remembrance and Identity in “Del corazón todavía”, by Silda Cordoliani (Castilla. Estudios de Literatura, 2012)
In “Del Corazón Todavía”, Silda Cordoliani builds a female character who feels challenged by her personal history. This character uses a variety of memory disorders such as amnesia, hipermnesia and paramnesia, to imagine a past according to the present that she wants to live. I propose to read this story by Silda Cordoliani, based on the book Dar cuenta de sí mismo (2009), by Judith Butler, to think the deshistorization as a pillar useful for creating an identity.